Theoretical priors in scalar-tensor cosmologies: thawing quintessence - García-García, C; Bellini, E; Ferreira, PG; Traykova, D; Zumalacarregui, M (American Physical Society, 2020)
The late time acceleration of the Universe can be characterized in terms of an extra, time-dependent, component of the Universe—dark energy. The simplest proposal for dark energy is a scalar-tensor theory—quintessence—which consists of a scalar field, ϕ, whose dynamics is solely dictated by its potential, V(ϕ). Such a theory can be uniquely characterized by the equation of state of the scalar field energy momentum-tensor. We find the time dependence of the equation of state for a broad family of potentials and, using this information, we propose an analytic prior distribution for the most commonly used parametrization. We show that this analytic prior can be used to accurately predict the distribution of observables for the next generation of cosmological surveys. Including the theoretical priors in the comparison with observations considerably improves the constraints on the equation of state.